Comparing the hypothalamic and extrahypothalamic actions of endogenous hyperleptinemia - Wang, Zhuo-Wei (The National Academy of Sciences, 1999)
To determine whether the depletion of body fat caused by adenovirus-induced hyperleptinemia is mediated via the hypothalamus, we used as a “bioassay” for hypothalamic leptin activity the hypothalamic expression of a leptin-regulated peptide, cocaine- and amphetamine-regulated transcript (CART). The validation of this strategy was supported by the demonstration that CART mRNA was profoundly reduced in obese rats with impaired leptin action, whether because of ablation of the ventromedial hypothalamus (VMH) or a loss-of-function mutation in the leptin receptor, as in Zucker diabetic fatty rats. We compared leptin activity in normal rats made hyperleptinemic by adenovirus-leptin treatment (43 ± 9 ng/ml, cerebrospinal fluid leptin 100 pg/ml) with normal rats made hyperleptinemic by a 60% fat intake (19 ± 4 ng/ml, cerebrospinal fluid leptin 69 ± 22 pg/ml). CART was increased 5-fold in the former and 2-fold in the latter, yet in adenovirus-induced hyperleptinemia, body fat had disappeared, whereas in high-fat-fed rats, body fat was abundant. Treatment of the high-fat-fed rats with adenovirus-leptin further increased their hyperleptinemia to 56 ± 6 ng/ml without changing CART mRNA or food intake, indicating that leptin action on hypothalamus had not been increased. Nevertheless, their body fat declined 36%, suggesting that an extrahypothalamic mechanism was responsible. We conclude that in diet-induced obesity body-fat depletion by leptin requires supraphysiologic plasma concentrations that exceed the leptin-transport capacity across the blood–brain barrier.